Institutional Capacity Building Of Disaster-Resilient Village in Garut Regency - Rd. Ahmad Buchari; Ivan Darmawan; Kurnia Muhamad Ramdhan (Iapa Proceedings Conference, 2019)
Disaster may occur anytime and anywhere, and is generally unpredictable. Therefore, the most important to do is disaster management to minimize any harmful impacts of disaster. To be more effective and efficient, it needs to involve all related parties. In regions, the relationship between village institutions is of high importance in disaster mitigation. This is because it is village administration (government) that is in direct relationship with community, and that the latter is one directly impacted by disasters in regions. Thus, in the context of disaster mitigation, the relationship between village institutions should be strengthened. Accordingly, the problem studied in the present research was, how is the strengthening of institutional relationships of villages in Garut Regency? The research method used was a qualitative method. The data collection techniques used were interview and observation. Interview was conducted with village officials and Destana volunteers. And observation was performed in the field on the activities conducted relating to disaster mitigation measures in the four villages which were the research objects, namely, Pasawahan, Rancabango, Mekarjaya, and Karyamekar. The research result revealed that the institutions in the four villages have been good enough but still need to be strengthened in the context of disaster management. The four villages were vulnerable to disasters and have had Destana instrument as a guard of disaster management at village level. In view of the research result, it is suggested that village officials improve their disaster management by, among others, conducting socialization on disaster risks, ways of lessening disaster occurrences, and ways of minimizing losses in case a disaster really occurs.